Black Americans' Perceptions of Communication and Other Factors during Oncology Care Virtual Visits: Presenter(s): Jennifer Elston Lafata, University of North Carolina at Chapel Hill, United States. (April 2023) - Rezk, Salma; Neslund-Dudas, Christine; Barrett, Amy; Tam, Samantha; Fridman, Ilona; Barrow, Lauren; Kinlaw, Alan; MIddlebrooks, William; Royce, Trevor; Smith, Angela; Stein, Jacob; Wood, William
Abstract : Background: During the COVID-19 pandemic, many oncology practices began offering virtual visits via video and/or telephone. How such visits are perceived by Black patients, who have historically faced access barriers and poorer cancer outcomes, is not known. We elicited Black patients' perceptions of and experiences with oncology virtual visits. Methods: We conducted in-depth, semi-structured telephone interviews with Black adults receiving oncology care for head and neck cancer, prostate cancer, and multiple myeloma between 6/1/19 - 3/20/21 from two US-based academic health systems. The interview guide elicited virtual visit perceptions and experiences within predefined themes (e.g., ease of use, usefulness, communication quality, appropriateness). Interviews were audio-recorded, transcribed, and coded for a priori themes and new ones identified during data immersion. Two trained research assistants coded transcripts, using Atlas.ti for data management. Findings: Forty-nine adults completed an interview between 9/2021 and 2/2022 (n=16 head and neck, n=16 prostate, and n=17 multiple myeloma); mean age 63 years (range: 39-75), 53% male, and 77% ever having a virtual visit. Participants indicated communication with their doctor and privacy was comparable between in-person and virtual visits but expressed feeling less human connectedness during virtual visits. They cited convenience advantages (e.g., being home, flexibility when physicians run late, and reduced travel barriers); however, they also reported preferring in-person visits, due to wanting doctors to conduct physical examinations or needing in-person testing. Participants described wanting a choice regarding visit type and valued it when physicians articulated the option to conduct an in-person visit (i.e., patient-centeredness in scheduling). To overcome technical barriers to virtual visit attendance, patients received assistance from adult children, physicians, and other support. Discussion: We identified barriers to and facilitators of virtual visit use among Black patients receiving cancer care.